Different effects of prenatal air pollution exposure on cord blood protein profiles and postnatal lung function in infants born to asthmatic mothers - Carla Rebeca Da Silva Sena; Olga Gorlanova; Noëmi Künstle; Gabriela Martins Costa Gomes; Andrea Marten; Sven Schulzke; Florian Wyler; Vanessa E. Murphy; Paul D. Robinson; Peter D. Sly; Jakob Usemann; Benjamin Stoecklin; et al. (Environmental Research, 2026)

Corrigendum to “Deep learning error post-processing improves stochastic watershed modeling” [J. Hydrol. 675 (2026) 135663] - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

Deep learning error post-processing improves stochastic watershed modeling - Benjamin Manoli; Sandeep Poudel; David K. Koval; Sarah Y. Murphy; Scott Steinschneider; Jonathan Lamontagne (Journal of Hydrology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Clinical Validation of Non-invasive Simulation-Based Determination of Vascular Impedance, Wave Intensity, and Hydraulic Work in Patients Undergoing Transcatheter Aortic Valve Replacement - Jonathan Y. Brown; Gabriela Veiga Fernandez; Jose M. De La Torre Hernández; Michael Murphy; Benjamin S. Wessler; Elazer R. Edelman (Annals of Biomedical Engineering, 2025)
Purpose The impact of Aortic Stenosis (AS) on the left ventricle (LV) extends beyond the influence of the pressure drop across the stenotic valve, but also includes the additional serial afterload imposed by the vascular system. Aortic input impedance is the gold standard for comprehensively studying the contribution of the vascular system to total myocardial afterload, but in the past measurement has been challenging arising from the need for invasive catheterization or specialized equipment to precisely record time-resolved blood pressure and flow signals. The goal of this work was to develop and validate a novel simulation-based method for determining aortic input impedance using only clinically available echocardiographic data and a simple blood pressure measurement. Methods A simulation-based method to determine vascular impedance was developed using echocardiographic data and a brachial blood pressure measurement. Simulation-based impedance was compared to impedance calculated from echocardiographic flow data and pressure data from a non-invasive central pressure measurement device. Results In validation analysis comparing patient-specific simulation-based vascular impedance to non-invasively measured impedance, correlation between methods across a range of vascular parameters varied between R 2 = 0.40 and 0.99. A tendency was seen toward underestimation of pressure waveforms in point-by-point comparison of measured and simulated waveforms with an overall mean difference of 4.01 mmHg. Conclusions Requiring only non-invasive clinical data that are widely available, simulation-based vascular impedance has the potential to allow for easier, more widespread, and larger-scale investigation of the effect of vascular impedance on total LV afterload.

TracMyAir smartphone application for modeling exposures to PM2.5 and ozone – Integration with air quality networks and location-activity sensors - Michael Breen; Vlad Isakov; Catherine Seppanen; Saravanan Arunachalam; Miyuki Breen; Steven Prince; Thomas Long; David Heist; Parikshit Deshmukh; K. Wyat Appel; Christian Hogrefe; Benjamin Murphy; et al. (Science of The Total Environment, 2025)

Bridging existing energy and chemical transport models to enhance air quality policy assessment - Stanley Ngo; Benjamin N. Murphy; Christopher G. Nolte; Kristen E. Brown (Environmental Modelling & Software, 2025)

Potential Exposure of Aquatic Organisms to Dynamic Visual Cues Originating from Aerial Wind Turbine Blades - Benjamin J. Williamson; Lonneke Goddijn-Murphy; Jason McIlvenny; Alan Youngson (Fishes, 2024)
For many aquatic species, vision is important for detecting prey, predators, and conspecifics; however, the potential impacts of visual cues from offshore wind turbines have not been investigated in these crucial contexts. There is the possibility of visual cues, originating from moving wind turbine blades, propagating through the air–water interface to impact visually sensitive species. Two classes of visual cues are possible: direct motion cues originating as light reflected from moving turbine blades and indirect cues resulting from an interruption of direct sunlight causing dynamic shadowing when the sun, blade, and receptor are aligned. In both cases, the propagation of cues across the air–water interface is governed by physical principles but modulated in potentially complex ways by the aspects of the local environment that vary with time. Evidence for the extent of the exposure of aquatic organisms to the visual cues arising from moving turbine blades and for the potential response of receptor organisms is sparse. This study considers the physics involved to support the formulation and testing of robust biological hypotheses. Marine migratory salmonid species are considered as an example species because their behaviour in the marine environment is relatively well documented. This study concludes that the aquatic receptor organisms present in the uppermost layer of the sea in the vicinity of wind turbines are potentially exposed to direct motion cues originating from moving turbine blades and also, when the sun elevation angle is greater than ca. 20°, to dynamic shadowing cues.

Occurrence of heavy metals coupled with elevated levels of essential elements in chocolates: Health risk assessment - Tewodros Rango Godebo; Hannah Stoner; Pornpimol Kodsup; Benjamin Bases; Sophia Marzoni; Jenna Weil; Matt Frey; Preston Daley; Alexa Earnhart; Gabe Ellias; Talia Friedman; Satwik Rajan; et al. (Food Research International, 2024)

Sensitivity of air quality to vehicle ammonia emissions in the United States - Claudia Toro; Darrell Sonntag; Jesse Bash; Guy Burke; Benjamin N. Murphy; Karl M. Seltzer; Heather Simon; Mark W. Shephard; Karen E. Cady-Pereira (Atmospheric Environment, 2024)

Enhancing agency and empowerment in agricultural development projects: A synthesis of mixed methods impact evaluations from the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) - Agnes R. Quisumbing; Ruth Meinzen-Dick; Hazel J. Malapit; Greg Seymour; Jessica Heckert; Cheryl Doss; Nancy Johnson; Deborah Rubin; Giang Thai; Gayathri Ramani; Emily Myers; Agnes Quisumbing; et al. (Journal of Rural Studies, 2024)

Recommendations for Method Development and Validation of qPCR and dPCR Assays in Support of Cell and Gene Therapy Drug Development - Amanda Hays; Mark Wissel; Kelly Colletti; Russell Soon; Mitra Azadeh; Justin Smith; Rajitha Doddareddy; Melanie Chalfant; Wendy Adamowicz; Swarna Suba Ramaswamy; Sanjay L. Dholakiya; Sebastian Guelman; et al. (The AAPS Journal, 2024)
The emerging use of qPCR and dPCR in regulated bioanalysis and absence of regulatory guidance on assay validations for these platforms has resulted in discussions on lack of harmonization on assay design and appropriate acceptance criteria for these assays. Both qPCR and dPCR are extensively used to answer bioanalytical questions for novel modalities such as cell and gene therapies. Following cross-industry conversations on the lack of information and guidelines for these assays, an American Association of Pharmaceutical Scientists working group was formed to address these gaps by bringing together 37 industry experts from 24 organizations to discuss best practices to gain a better understanding in the industry and facilitate filings to health authorities. Herein, this team provides considerations on assay design, development, and validation testing for PCR assays that are used in cell and gene therapies including (1) biodistribution; (2) transgene expression; (3) viral shedding; (4) and persistence or cellular kinetics of cell therapies. Graphical Abstract

Predictions of PFAS regional-scale atmospheric deposition and ambient air exposure - Emma L. D'Ambro; Benjamin N. Murphy; Jesse O. Bash; Robert C. Gilliam; Havala O.T. Pye (Science of The Total Environment, 2023)

Daily activity timing in the Anthropocene - Neil A. Gilbert; Kate A. McGinn; Laura A. Nunes; Amy A. Shipley; Jacy Bernath-Plaisted; John D.J. Clare; Penelope W. Murphy; Spencer R. Keyser; Kimberly L. Thompson; Scott B. Maresh Nelson; Jeremy M. Cohen; Ivy V. Widick; et al. (Trends in Ecology & Evolution, 2023)

Comparative spatially explicit approach for testing effects of soil chemicals on terrestrial wildlife bioindicator demographics - Sean M. Murphy; Charles D. Hathcock; Tatiana N. Espinoza; Philip R. Fresquez; Jesse T. Berryhill; Jenna E. Stanek; Benjamin J. Sutter; Shannon M. Gaukler (Environmental Pollution, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Heuristic Approach for Inter-Facility Comparison of Results from Round Robin Testing of a Floating Wind Turbine in Irregular Waves - Sebastien Gueydon; Frances Judge; Eoin Lyden; Michael O’Shea; Florent Thiebaut; Marc Le Boulluec; Julien Caverne; Jérémy Ohana; Benjamin Bouscasse; Shinwoong Kim; Sandy Day; Saishuai Dai; et al. (Journal of Marine Science and Engineering, 2021)
This paper introduces metrics developed for analysing irregular wave test results from the round robin testing campaign carried out on a floating wind turbine as part of the EU H2020 MaRINET2 project. A 1/60th scale model of a 10 MW floating platform was tested in wave basins in four different locations around Europe. The tests carried out in each facility included decay tests, tests in regular and irregular waves with and without wind thrust, and tests to characterise the mooring system as well as the model itself. While response amplitude operations (RAOs) are a useful tool for assessing device performance in irregular waves, they are not easy to interpret when performing an inter-facility comparison where there are many variables. Metrics that use a single value per test condition rather than an RAO curve are a means of efficiently comparing tests from different basins in a more heuristic manner. In this research, the focus is on using metrics to assess how the platform responds with varying wave height and thrust across different facilities. It is found that the metrics implemented are very useful for extracting global trends across different basins and test conditions.

Round Robin Laboratory Testing of a Scaled 10 MW Floating Horizontal Axis Wind Turbine - Sebastien Gueydon; Frances M. Judge; Michael O’Shea; Eoin Lyden; Marc Le Boulluec; Julien Caverne; Jérémy Ohana; Shinwoong Kim; Benjamin Bouscasse; Florent Thiebaut; Sandy Day; Saishuai Dai; et al. (Journal of Marine Science and Engineering, 2021)
This paper documents the round robin testing campaign carried out on a floating wind turbine as part of the EU H2020 MaRINET2 project. A 1/60th scale model of a 10 MW floating platform was tested in wave basins in four different locations around Europe. The tests carried out in each facility included decay tests, tests in regular and irregular waves with and without wind thrust, and tests to characterise the mooring system as well as the model itself. For the tests in wind, only the thrust of the turbine was considered and it was fixed to pre-selected levels. Hence, this work focuses on the hydrodynamic responses of a semi-submersible floating foundation. It was found that the global surge stiffness was comparable across facilities, except in one case where different azimuth angles were used for the mooring lines. Heave and pitch had the same stiffness coefficient and periods for all basins. Response Amplitude Operators (RAOs) were used to compare the responses in waves from all facilities. The shape of the motion RAOs were globally similar for all basins except around some particular frequencies. As the results were non-linear around the resonance and cancellation frequencies, the differences between facilities were magnified at these frequencies. Surge motions were significantly impacted by reflections leading to large differences in these RAOs between all basins.

Turbines and Terrestrial Vertebrates: Variation in Tortoise Survivorship Between a Wind Energy Facility and an Adjacent Undisturbed Wildland Area in the Desert Southwest (USA) - Mickey Agha; Jeffrey E. Lovich; Joshua R. Ennen; Benjamin Augustine; Terence R. Arundel; Mason O. Murphy; Kathie Meyer-Wilkins; Curtis Bjurlin; David Delaney; Jessica Briggs; Meaghan Austin; Sheila V. Madrak; et al. (Environmental Management, 2015)

Biodegradation of polyfluorinated biphenyl in bacteria - David Hughes; Benjamin R. Clark; Cormac D. Murphy (Biodegradation, 2011)

Subsurface Carbon Contents: Some Case Studies in Forest Soils - Dale W. Johnson; James D. Murphy; Benjamin M. Rau; Watkins W. Miller (Forest Science, 2011)
This article evaluates the importance of deeper soil horizons for soil C inventories in forest ecosystems. For non-Spodosols, we categorized soils as to the degree of convexity of the cumulative soil C content profile. Soils with a highly convex or asymptotic soil C content profile contained a significantly lower fraction of their total C (36 ± 8%) below 20 cm than those with less convex (nonasymptotic) profiles (51 ± 2%), even though the more convex soils were 12 cm (23%) deeper. Spodosols contained the most C below 20 cm (66 ± 3%) as a result of the presence of spodic horizons. Spodosols also contained substantially more total soil profile C than non-Spodosols even though the average depths of sampling were similar. Langmuir and logarithmic equations predicted C contents of deeper horizons fairly well for most non-Spodosol soils, whereas C content declines systematically with depth. These equations were very poor for Spodosols, however, because of the increases in soil C with depth that often occur with spodic horizons. Two case studies from the Sierra Nevada mountains suggested that C concentration varies to a greater degree than does bulk density or fine earth (% <2 mm) content, thus illustrating the importance of obtaining good estimates of the large stone content, which can offset differences in C concentration when C content is calculated in the normal fashion (i.e., ignoring the >2-mm fraction). These case studies do not support the idea of estimating bulk density from soil C concentration.

Basal Ganglia MR Relaxometry in Obsessive-Compulsive Disorder: T2 Depends Upon Age of Symptom Onset - Stephen Correia; Emily Hubbard; Jason Hassenstab; Agustin Yip; Josef Vymazal; Vit Herynek; Jay Giedd; Dennis L. Murphy; Benjamin D. Greenberg (Brain Imaging and Behavior, 2010)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Attenuated response to m -CPP and to pentagastrin after repeated m -CPP in panic disorder - J. Benjamin; Marilla Geraci; Una McCann; Benjamin D. Greenberg; Dennis L. Murphy (Psychopharmacology, 1999)

Delayed obsessive-compulsive disorder symptom exacerbation after a single dose of a serotonin antagonist in fluoxetine-treated but not untreated patients - B. D. Greenberg; Jonathan Benjamin; Juliet D. Martin; David Keuler; S.-J. Huang; Margaret Altemus; Dennis L. Murphy (Psychopharmacology, 1998)